Increasing outdoor host-seeking in Anopheles gambiae over 6 years of vector control on Bioko Island. (December 2016) - Meyers, Jacob; Pathikonda, Sharmila; Popkin-Hall, Zachary; Medeiros, Matthew; Fuseini, Godwin; Matias, Abrahan; Garcia, Guillermo; Overgaard, Hans; Kulkarni, Vani; Reddy, Vamsi; Schwabe, Christopher; Lines, Jo; et al.
Abstract Background Vector control through indoor residual spraying (IRS) has been employed on Bioko Island, Equatorial Guinea, under the Bioko Island Malaria Control Project (BIMCP) since 2004. This study analyses the change in mosquito abundance, species composition and outdoor host-seeking proportions from 2009 to 2014, after 11 years of vector control on Bioko Island. Methods All-night indoor and outdoor human landing catches were performed monthly in the Bioko Island villages of Mongola, Arena Blanca, Biabia and Balboa from 2009 to 2014. Collected mosquitoes were morphologically identified and a subset ofAnopheles gambiae sensu lato (s.l. ) were later identified molecularly to their sibling species. Mosquito collection rates, species composition and indoor/outdoor host-seeking sites were analysed using generalized linear mixed models to assess changes in mosquito abundance and behaviour. Results The overall mosquito collection rate declined in each of the four Bioko Island villages.Anopheles coluzzii andAnopheles melas comprised theAn. gambiae s.l. mosquito vector population, with a range of species proportions across the four villages. The proportion of outdoor host-seekingAn. gambiae s.l. mosquitoes increased significantly in all four villages with an average increase of 58.8 % [57.9, 59.64 %] in 2009 to 70.0 % [67.8, 72.0 %] in 2014. Outdoor host-seeking rates did not increase in the month after an IRS spray round compared to the month before, suggesting that insecticide repellency has little impact on host-seeking behaviour. Conclusion While vector control on Bioko Island has succeeded in substantial reduction in overall vector biting rates, populations ofAn. coluzzii andAn. melas persist. Host-seeking behaviour has changed in theseAn. gambiae s.l. populations, with a shift towards outdoor host-seeking. During this study period, the proportion of host-seekingAn. gambiae s.l. caught outdoors observed on Bioko Island increased to high levels, exceeding 80 % in some locations. It is possible that there may be a genetic basis underlying this large shift in host-seeking behaviour, in which case outdoor feeding could pose a serious threat to current vector control programmes. Currently, the BIMCP is preparing for this potential challenge by testing source reduction as a complementary control effort that also targets outdoor transmission.